Motivated Beliefs: Evidence from an Experiment on Climate-Smart Dairy in the UK - Kiplagat, Walter; Maertens, Annemie; Hidalgo, Daniel Enriquez; Barker, Zoe; Gadanakis, Yiorgos; Reynolds, Chris; Hall, Sara; Laepple, Doris (My University, 2024)
The UK dairy sector strives for net-zero by 2050. This implies the adoption of climate-smart technologies, which improve efficiency, reduce emissions, and build carbon storage. We assess how consumers perceive these technologies, i.e. their knowledge and preferences, and how much they are willing-to-pay for milk produced using smart-dairy technologies. We distinguish between three different avenues: a nature-based approach which increases carbon sequestration, a technology-based approach which improves system efficiency, and an emission-reduction-based approach which tackles emissions directly at the source. We set up a laboratory experiment with three information treatments – labels, posters, and videos. We collect data on knowledge, stated preferences and willingness-to-pay before and after the information interventions. Results suggest a lack of effects of the video and poster interventions (as opposed to the generic label) to increase willingness-to-pay, although significant effects are found on knowledge and stated preferences. The participants slightly prefer nature-based approaches, and videos increase these preferences. Both posters and videos also increase stated preferences for the nature-based and emission-reduction-based approaches. These results support theories of motivated and anchored beliefs: when receiving more information, biases are confirmed towards nature-based approaches; and preferences and knowledge respond together when learning about the more unknown emission-reduction approaches.
Keywords: Dairy farming; Climate Change; UK; Consumer Preferences